Activation of cellular immune responses using a dengue tetravalent subunit DNA vaccine candidate with different cytokines as adjuvants - Luciana de Souza Fernandes; Carine Ribeiro Pessoa; Roberto Sousa Dias; Cynthia Canedo da Silva; Sérgio Oliveira de Paula (Vaccine: X)
Dengue remains a critical public health issue in endemic areas, with four co-circulating serotypes (DENV-1–4) and no widely accessible vaccine in Brazil. DNA vaccines offer logistical and cost advantages, and cytokine adjuvants may enhance immunogenicity. We engineered a tetravalent DNA vaccine encoding EDIII from all four DENV serotypes in the pVAX1 vector. To improve immune response, plasmids encoding GM-CSF, IL-7, and IL-15 were co-administered. Antigen expression was confirmed via PCR, western blot, and immunofluorescence. Immunogenicity was assessed using lymphoproliferation assays, TNF/IL-10 cytokine profiling, flow cytometry for memory T-cell phenotyping, and plaque reduction neutralization tests (PRNT). EDIII expression was confirmed for all four serotypes. Co-administration with GM-CSF or IL-15 increased splenocyte proliferation. Cytokine analysis showed variable results with Th1-skewed responses in IL-7 and GM-CSF groups, while IL-15 induced a Th2-biased profile. Flow cytometry revealed that GM-CSF + IL-15 most effectively expanded central memory and naïve CD4+ and CD8+ T cells. PRNT demonstrated neutralizing activity against DENV-1, DENV-3, and DENV-4, but no neutralization of DENV-2. This tetravalent DNA vaccine elicited modest antigen-specific humoral and cellular responses. GM-CSF and IL-15 improved T-cell memory phenotypes, although the absence of DENV-2 neutralization highlights the need for further optimization. Our results inform us of the difficulties in using immune modulators as genetic adjuvants for DNA vaccine design.